Perinatal Fluoxetine Exposure Impairs the co2 Chemoreflex Implications for Sudden Infant Death Syndrome - Eugenin-Leon, J; Llona-Rodriguez, I; Bravo-Flores, K (American Thoracic Society, 2016)
High serotonin levels during pregnancy affect central nervous system development. Whether a commonly used antidepressant such as fluoxetine (a selective serotonin reuptake inhibitor) taken during pregnancy may adversely affect respiratory control in offspring has not been determined. The objective was to determine the effect of prenatal-perinatal fluoxetine exposure on the respiratory neural network in offspring, particularly on central chemoreception. Osmotic minipumps implanted into CF-1 mice on Days 5-7 of pregnancy delivered 7 milligrams per kilogram per day of fluoxetine, achieving plasma levels within the range found in patients. Ventilation was assessed in offspring at postnatal Days 0-40 using head-out body plethysmography. Neuronal activation was evaluated in the raphe nuclei and in the nucleus tractus solitarius by c-Fos immunohistochemistry during normoxic eucapnia and hypercapnia (10% CO2). Respiratory responses to acidosis were evaluated in brainstem slices. Prenatal-perinatal fluoxetine did not affect litter size, birth weight, or the postnatal growth curve. Ventilation under eucapnic normoxic conditions was similar to that of control offspring. Fluoxetine exposure reduced ventilatory responses to hypercapnia at P8-P40 (P,0.001) but not at P0-P5. At P8, it reduced hypercapnia-induced neuronal activation in raphe nuclei (P,0.05) and nucleus tractus solitarius (P,0.01) and the acidosisinduced increase in the respiratory frequency in brainstem slices (P,0.05). Fluoxetine applied acutely on control slices did not modify their respiratory response to acidosis. We concluded that prenatal-perinatal fluoxetine treatment impairs central respiratory chemoreception during postnatal life. These results are relevant in understanding the pathogenesis of respiratory failures, such as sudden infant death syndrome, associated with brainstem serotonin abnormalities and the failure of respiratory chemoreflexes. © 2016 by the American Thoracic Society.